Palynological evidence of sea-surface conditions in the Barents Sea off northeast Svalbard during the postglacial period - Brice, Camille; De Vernal, Anne; Ivanova, Elena; Van Bellen, Simon; Van Nieuwenhove, Nicolas (Quaternary Research, 2022)
Abstract Postglacial changes in sea-surface conditions, including sea-ice cover, summer temperature, salinity, and productivity were reconstructed from the analyses of dinocyst assemblages in core S2528 collected in the northwestern Barents Sea. The results show glaciomarine-type conditions until about 11,300 ± 300 cal yr BP and limited influence of Atlantic water at the surface into the Barents Sea possibly due to the proximity of the Svalbard-Barents Sea ice sheet. This was followed by a transitional period generally characterized by cold conditions with dense sea-ice cover and low-salinity pulses likely related to episodic freshwater or meltwater discharge, which lasted until 8700 ± 700 cal yr BP. The onset of “interglacial” conditions in surface waters was marked by a major change in dinocyst assemblages, from dominant heterotrophic to dominant phototrophic taxa. Until 4100 ± 150 cal yr BP, however, sea-surface conditions remained cold, while sea-surface salinity and sea-ice cover recorded large amplitude variations. By ~4000 cal yr BP optimum sea-surface temperature of up to 4°C in summer and maximum salinity of ~34 psu suggest enhanced influence of Atlantic water, and productivity reached up to 150 gC/m 2 /yr. After 2200 ± 1300 cal yr BP, a distinct cooling trend accompanied by sea-ice spreading characterized surface waters. Hence, during the Holocene, with exception of an interval spanning about 4000 to 2000 cal yr BP, the northern Barents Sea experienced harsh environments, relatively low productivity, and unstable conditions probably unsuitable for human settlements.

Distribution and (palaeo)ecological affinities of the main Spiniferites taxa in the mid-high latitudes of the Northern Hemisphere - De Vernal, Anne; Eynaud, Frédérique; Henry, Maryse; Limoges, Audrey; Londeix, Laurent; Matthiessen, Jens; Marret, Fabienne; Pospelova, Vera; Radi, Taoufik; Rochon, André; Van Nieuwenhove, Nicolas; Zaragosi, Sébastien (Palynology, 2018)

An overview and brief description of common marine organic-walled dinoflagellate cyst taxa occurring in surface sediments of the Northern Hemisphere - Van Nieuwenhove, Nicolas; Head, Martin J.; Limoges, Audrey; Pospelova, Vera; Mertens, Kenneth N.; Matthiessen, Jens; De Schepper, Stijn; De Vernal, Anne; Eynaud, Frédérique; Londeix, Laurent; Marret, Fabienne; Penaud, Aurélie; et al. (Marine Micropaleontology, 2020)

Distribution of common modern dinoflagellate cyst taxa in surface sediments of the Northern Hemisphere in relation to environmental parameters: The new n=1968 database - De Vernal, Anne; Radi, Taoufik; Zaragosi, Sebastien; Van Nieuwenhove, Nicolas; Rochon, André; Allan, Estelle; De Schepper, Stijn; Eynaud, Frédérique; Head, Martin J.; Limoges, Audrey; Londeix, Laurent; Marret, Fabienne; et al. (Marine Micropaleontology, 2020)

The dinoflagellate cyst genera Achomosphaera Evitt 1963 and Spiniferites Mantell 1850 in Pliocene to modern sediments: a summary of round table discussions - Mertens, Kenneth Neil; Van Nieuwenhove, Nicolas; Gurdebeke, Pieter R.; Aydin, Hilal; Bogus, Kara; Bringué, Manuel; Dale, Barrie; De Schepper, Stijn; De Vernal, Anne; Ellegaard, Marianne; Grothe, Arjen; Gu, Haifeng; et al. (Palynology, 2018)